CHALLENGES OF IOT INTEGRATION INTO COMPUTER NETWORKS - Pohrebniak, A. V.; Yakovenko, V. O.; Klym, V. Yu.; Yakovenko, T. Yu. (Systems and Technologies, 2024)
This article examines the results of a study on the integration of Internet of Things (IoT) technologies, which enables interconnection among physical devices and exchange data over networks without human intervention. The paper reviews several fundamental research articles covering various aspects of IoT, from its architecture to security challenges. An analysis of IoT integration research indicates the rapid evolution of this technology addressing multiple aspects ranging from architecture to security. Highlight the significance of developing standards, protocols, and technologies to ensure secure and efficient IoT integration across various fields, unlocking potential for future innovation and advancement. The research aims to analyze key challenges of IoT integration into computer networks and suggests potential solutions to overcome them. Objectives within this aim include providing an overview of the global network of internet-connected devices that exchange data and interact with each other, identifying the primary components and layers comprising its architecture, comparing network technologies in terms of scalability, and analyzing major cyber threats to IoT. Further goals include examining assessing the effect of different IoT system types on network bandwidth, detailing key protocols used by IoT devices, analyzing the benefits of Software-Defined Networking (SDN) for scalability issues, identifying key IoT protection methods, comparing bandwidth for different IoT systems, recommending energy-efficient technologies for autonomous IoT device operation, and comparing bandwidth and latency levels for various types of IoT networks. Data protection and IoT network security remain significant challenges due to the increased vulnerability to cyberattacks from a high number of connected devices. Modern encryption, authentication, and network segmentation methods are crucial for enhancing IoT system security. IoT integration into computer networks creates new opportunities for developing intelligent systems across various domains, from smart cities to industrial production. However, successful implementation requires addressing these challenges and applying appropriate solutions to overcome them.